Roles of epithelial cell-derived periostin in TGF-β activation, collagen production, and collagen gel elasticity in asthma - Sidhu, Sukhvinder S.; Yuan, Shaopeng; Innes, Anh L.; Kerr, Sheena; Woodruff, Prescott G.; Hou, Lydia; Muller, Susan J.; Fahy, John V.; Yamamoto, Keith R. (Proceedings of the National Academy of Sciences - PNAS, 2010)
Periostin is considered to be a matricellular protein with expression typically confined to cells of mesenchymal origin. Here, by using in situ hybridization, we show that periostin is specifically up-regulated in bronchial epithelial cells of asthmatic subjects, and in vitro, we show that periostin protein is basally secreted by airway epithelial cells in response to IL-13 to influence epithelial cell function, epithelial–mesenchymal interactions, and extracellular matrix organization. In primary human bronchial epithelial cells stimulated with periostin and epithelial cells overexpressing periostin, we reveal a function for periostin in stimulating the TGF-β signaling pathway in a mechanism involving matrix metalloproteinases 2 and 9. Furthermore, conditioned medium from the epithelial cells overexpressing periostin caused TGF-β–dependent secretion of type 1 collagen by airway fibroblasts. In addition, mixing recombinant periostin with type 1 collagen in solution caused a dramatic increase in the elastic modulus of the collagen gel, indicating that periostin alters collagen fibrillogenesis or cross-linking and leads to stiffening of the matrix. Epithelial cell-derived periostin in asthma has roles in TGF-β activation and collagen gel elasticity in asthma.